1997
DOI: 10.1007/bf02418978
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effectiveness of iodine carbon adsorbers in special ventilation systems of nuclear power plants with rbmk-1000 reactors

Abstract: Carbon filters--adsorbers are used in the third and fourth power-generating units of the second phase of the Leningrad nuclear power plant for catching gaseous and aerosol forms of radioactive iodine. They are installed in VTs-4 and -8 ventilation systems, where air enters from the space below the equipment and enclosures of the bottom water pipes, blowoff from the stub of the unloading-loading machine and the tank for emptying it, as well as cases with nonhermetic fuel assemblies. The airflow into ventilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In practice, Petryanov filtering fabric based on perchlorovinyl polymer fibers in moist media becomes wet and loses its filtering properties. FPP material does not meet the fire safety and toxicity requirements [10], since it is combustible, and toxic substances are formed when it burns.Analysis of the efficiency of filters and carbon adsorbers, operating in the special ventilation systems of a nuclear power plant, has shown that the systems for removing aerosols and volatile compounds of iodine from steam-air media need to the improved because the removal efficiency is low and does not meet modern requirements [10,11]. The removal efficiency is 93-96% for radioactive aerosols and 28-94% for volatile forms of iodine but in most cases it is 67-83%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, Petryanov filtering fabric based on perchlorovinyl polymer fibers in moist media becomes wet and loses its filtering properties. FPP material does not meet the fire safety and toxicity requirements [10], since it is combustible, and toxic substances are formed when it burns.Analysis of the efficiency of filters and carbon adsorbers, operating in the special ventilation systems of a nuclear power plant, has shown that the systems for removing aerosols and volatile compounds of iodine from steam-air media need to the improved because the removal efficiency is low and does not meet modern requirements [10,11]. The removal efficiency is 93-96% for radioactive aerosols and 28-94% for volatile forms of iodine but in most cases it is 67-83%.…”
mentioning
confidence: 99%
“…Analysis of the efficiency of filters and carbon adsorbers, operating in the special ventilation systems of a nuclear power plant, has shown that the systems for removing aerosols and volatile compounds of iodine from steam-air media need to the improved because the removal efficiency is low and does not meet modern requirements [10,11]. The removal efficiency is 93-96% for radioactive aerosols and 28-94% for volatile forms of iodine but in most cases it is 67-83%.…”
mentioning
confidence: 99%